Preparation and physicochemical properties of sodium carboxymethyl mungbean starches - Ornanong S. Kittipongpatana (2018)
Fifteen sodium carboxymethyl mungbean starches (SCMMSs or MMSs) were prepared from native starch through a substitution reaction using monochloroacetic acid, using different modification conditions and solvents. Physicochemical properties, including the determination of degree of substitution, solubility studies, SEM and X-ray diffraction analyses, and rheological studies under normal and freeze-thaw conditions were investigated. The degree of substitution (DS) of the prepared MMSs ranged from 0.06-0.66. Nine modified mungbean starches were freely soluble in unheated water while the other six were partially soluble or only swelled. The pH of water-soluble MMSs were between 9.0-10.5. Scanning electron microscopy (SEM) pictures showed that the particles of all of the soluble modified starches were mostly ruptured, with the exception of MMS-M-04 and MMS-E-04 for which the starch granules remained rounded. X-ray diffraction results concurred with the SEM findings, showing that all the rounded-particle MMSs retained their crystallinity while those with destroyed surface SEMs showed loss of crystallinity. Ethanol (92.4%) appeared to be the most effective solvent in the preparation but the condition that yielded modified starches with the most viscous paste was methanol (100%) at 70 °C for 60 min. The potential applications of these modified starches in food and pharmaceutical industries are discussed. © 2005 Elsevier Ltd. All rights reserved.